Relação amônio e nitrato, mitigação da toxicidade amoniacal com silício e curva de acúmulo de nutrientes em mudas de maracujazeiro - Silva Júnior, Gabriel Barbosa da [UNESP] (2015)
Studies on yellow passion fruit seedlings nutrition involving ammonium nitrate proportions and the ammonium toxicity and nutrient accumulation curve are incipient in the literature. In this sense, aimed to evaluate: ammonium nitrate proportions, the interaction between silicon and ammonium excess end the accumulation of nutrients and Si during the growing of yellow passion fruit seedlings. The experiment was conducted in a greenhouse at São Paulo State University, Jaboticabal, from February to Octuber, 2014, starting at three steps: First experiment: the treatments followed a 4 x 5 factorial design, consisting of four nitrogen concentrations: 2.5; 5.0; 10.0 and 20.0 mmol L-1 and five ammonium proportions: 0; 25; 50; 75 and 100%, relative to nitrate, arranged in a randomized block design with three replications. It was evaluated: green color index, nitrogen, potassium, calcium and magnesium accumulation in roots and shoots, stem diameter, leaf area, root length and nitrogen use efficiency and dry matter of root and shoot. Second experiment: the treatments followed a 2 x 2 factorial design, corresponding to two proportions of ammonium and nitrate (40/60%, without excess ammonium; and 75/25%, excess ammonium) in the absence and presence of Si, arranged in completely randomized design, with five repetitions. It was avaluated: N, Si, K, Ca and Mg accumulation in the root and shoot; leaves green color index; electrolyte leakage rate, internal CO2 concentration, transpiration, stomatal conductance, photosynthesis, stem diameter, leaf area, root length, nitrogen use efficiency and dry matter of root and shoot; Third experiment: It was used seven treatments, consisting of the seedling cultivation times: 0; 10; 20; 30; 40; 50, corresponding to 0; 175; 330; 585; 785; 980 and 1175 degrees day, respectively, arranged in a completely randomized design, with eight replications. In each time of cultivation were evaluated: organogenic net ...